Characteristics associated with the application of an ecological approach to preventing childhood obesity - Stark, Christina M; Devine, Carol M; Dollahite, Jamie S (Public health nutrition, 2017)
Applying an ecological approach to childhood obesity prevention requires a new way of thinking and working for many community-based practitioners who are used to focusing on individual behaviour change. The present study investigated individual and organizational characteristics associated with the application of an ecological approach by practitioners 6 months post-training. Individual and organizational characteristics and outcomes of a 6-week online training course were assessed at pre-course, post-course and 6-month follow-up. The application of an ecological approach was measured by three outcomes (application of course content, implementation of an action plan and trying a different approach) and analysed using a generalized estimating equation model with a binomial distribution and logit link and linear mixed models. An online course for participants in the USA and abroad. Public health nutrition and youth development educators and their community partners, and other community practitioners, who completed the course and all three surveys (n 240). One individual characteristic (networking utility) and three organizational characteristics (ecological approach within job scope, funding, course content applied to work) were positively and significantly associated with the application of an ecological approach (P<0·05). Individual characteristics that were negatively and significantly associated with the application of an ecological approach were being a registered dietitian and having ≥16 years of work experience (P<0·05). Training of community practitioners and the scope and funding of their positions should explicitly emphasize the usefulness or utility of networking and the use of an ecological approach for preventing childhood obesity.